Exploring the ring current of carbon nanotubes by first-principles calculations. Issue 2 (26th September 2014) - Ren, Pengju; Zheng, Anmin; Xiao, Jianping; Pan, Xiulian; Bao, Xinhe
Abstract : The ring currents by the axial component of B0 depend on the semiconducting or metallic properties of CNTs and hence determine the overall magnetic responses and the aromatic characters. Abstract : Ring current is a fundamental concept to understand the nuclear magnetic resonance (NMR) properties and aromaticity for conjugated systems, such as carbon nanotubes (CNTs). Employing the recently developed gauge including projector augmented wave (GIPAW) method, we studied the ring currents of CNTs systematically and visualized their distribution. The ring current patterns are determined by the semiconducting or metallic properties of CNTs. The discrepancy is mainly caused by the axial component of external magnetic fields, whereas the radial component induced ring currents are almost independent of the electronic structures of CNTs, where the intensities of the ring currents are linearly related to the diameters of the CNTs. Although the ring currents induced by the radial component are more intense than those by the axial component, only the latter determines the overall NMR responses and aromaticity of the CNTs as well. Furthermore, the semiconducting CNTs are more aromatic than their metallic counterparts due to the existence of delocalized ring currents on the semiconducting CNTs. These fundamental features are of vital importance for the development of CNT-based nanoelectronics and applications in magnetic fields.